2012
DOI: 10.1002/jsfa.5624
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of antioxidant compounds in sweet bell pepper (Capsicum annuum L.) under organic and conventional growing systems

Abstract: Organic growing increased the level of antioxidant compounds such as carotenoids, phenolic compounds and vitamin C in sweet bell pepper. The second significant factor affecting the antioxidant compound content of sweet bell pepper was variety. It would be necessary to continue this study as a long-term experiment in order to eliminate the influence of seasonality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
7
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 27 publications
11
100
7
2
Order By: Relevance
“…Low content of nutrients in the organic solutions could cause nutritional stress in cucumber plants during growth, promoting increases of phenolic compounds production, thereby resulting in a higher antioxidant capacity of organic fruits. Moreover, it has been reported that the production of nitrogen-containing compounds such as amino acids, proteins and alkaloids increases in crops under production systems sufficient in nitrogen supply (Hallmann and Rembiałkowska 2012). Nevertheless, Herms and Mattson (1992) state that plants produce higher amounts of sugars (simple and complex) and secondary metabolites (pigments, vitamins, organic acids, terpenoides and phenolic compounds) when subjected to a deficit of soluble nitrogen supply, which happened in the present study in cucumber plants fertilized with the organic nutrient solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Low content of nutrients in the organic solutions could cause nutritional stress in cucumber plants during growth, promoting increases of phenolic compounds production, thereby resulting in a higher antioxidant capacity of organic fruits. Moreover, it has been reported that the production of nitrogen-containing compounds such as amino acids, proteins and alkaloids increases in crops under production systems sufficient in nitrogen supply (Hallmann and Rembiałkowska 2012). Nevertheless, Herms and Mattson (1992) state that plants produce higher amounts of sugars (simple and complex) and secondary metabolites (pigments, vitamins, organic acids, terpenoides and phenolic compounds) when subjected to a deficit of soluble nitrogen supply, which happened in the present study in cucumber plants fertilized with the organic nutrient solutions.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that the application of different levels of the macronutrient nitrogen via fertigation does not affect the phenolic content of melon fruits obtained under open field conditions (Ferrante et al, 2008). Other researchers have reported that the production of nitrogen-containing compounds, such as amino acids, proteins and alkaloids, increases in crops under production systems with a sufficient nitrogen supply (Hallmann and Rembiałkowska, 2012). Nevertheless, Herms and Mattson (1992) found that plants produce greater amounts of sugars (simple and complex) and secondary metabolites (pigments, vitamins, organic acids, terpenoides and phenolic compounds) when subjected to a deficit of the soluble nitrogen supply, which occurred in the present study in the melon plants fertilized with the organic nutrient solutions.…”
Section: Analytical Testsmentioning
confidence: 99%
“…Moreover, consumption of organic food products has increased recently because consumers are demanding high-quality fresh products that are safe and pesticide-free (Hallmann and Rembiałkowska, 2012) and are produced using environmentally friendly production systems (Bourn and Prescott, 2002;Zhao et al, 2006). An additional advantage of organic horticultural produce is its better nutraceutical quality due to higher contents of ascorbic acid, phenolics, total sugars and antioxidant compounds (Guerrero et al, 2010;Hallmann and Rembiałkowska, 2012). A nutraceutical is any substance that is a food or a part of food that provides medical or health benefits, including prevention and treatment of disease (DeFelice, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the increase in compared to their conventional counterparts. The differences concern mainly higher sensory quality of organic fruits and vegetables, as well as the higher content of polyphenolic compounds and vitamins in organic agricultural crops compared to conventional ones (Asami et al, 2003;Bavec et al, 2010;Hallmann and Rembiałkowska, 2012;Średnicka-Tober et al, 2013;Kazimierczak et al, 2014). This is mainly due to different fertilization and crop protection regimes used in organic and conventional production systems.…”
Section: Introductionmentioning
confidence: 99%